PB

Tính:

1 - 0 =     1 - 1 =     5 - 1 =

2 - 0 =     2 - 2 =     5 - 2 =

3 - 0 =     3 - 3 =     5 - 3 =

4 - 0 =     4 - 4 =     5 - 4 =

5 - 0 =     5 - 5 =     5 - 5 =

CT
2 tháng 5 2019 lúc 12:32

1 - 0 = 1     1 - 1 = 0     5 - 1 = 4

2 - 0 = 2     2 - 2 = 0     5 - 2 = 3

3 - 0 = 3     3 - 3 = 0     5 - 3 = 2

4 - 0 = 4     4 - 4 = 0     5 - 4 = 1

5 - 0 = 5     5 - 5 = 0     5 - 5 = 0

Bình luận (0)
H24
4 tháng 1 2023 lúc 20:32

1 - 0 = 1     1 - 1 = 0     5 - 1 = 4

2 - 0 = 2     2 - 2 = 0     5 - 2 = 3

3 - 0 = 3     3 - 3 = 0     5 - 3 = 2

4 - 0 = 4     4 - 4 = 0     5 - 4 = 1

5 - 0 = 5     5 - 5 = 0     5 - 5 = 0

Bình luận (0)

Các câu hỏi tương tự
PB
Xem chi tiết
PB
Xem chi tiết
PB
Xem chi tiết
PB
Xem chi tiết
PB
Xem chi tiết
PB
Xem chi tiết
PB
Xem chi tiết
PB
Xem chi tiết
PB
Xem chi tiết